Cavernous hemangioma of the knee - case report - Weiss, Marcin; Dolata, Tomasz; Weiss, Waldemar; Maksymiak, Martyna; Kałużny, Krystian; Kałużna, Anna; Żukow, Walery; Hagner-Derengowska, Magdalena (Journal of Education, Health and Sport, 2018)
Introduction: Cavernous hemangiomas are uncommon lesions and, as such, may enter the differential diagnosis of other lesions encountered more frequently in clinical practice, including pigmented villonodular synovitis and traumatic hemarthrosis. Case report: A 21 year old single Polish woman who presented a non specific chronic knee tumefaction secondary to cavernous angioma confirmed radiologically and histologically, with a quite good evolution after surgery. Summation: Cavernous hemangioma of the knee is a frequently misdiagnosed lesion. MRI is the exploration of choice for this vascular tumor of the synovial membrane, although a pathology study is needed to confirm the diagnosis. Early surgical treatment with excision of the tumor within wide margins of uninvolved normal synovial tissue as partial or total synovectomy is the therapy of choice.